Tutorial de DSpace-CRIS - Mornati, Susanna (2018)
DSpace-CRIS is an “extended” version of DSpace, the most adopted repository platform in the world.It has a powerful and flexible data model to describe not just publications, but all the entities that populate the research environment and their meaningful relationships. DSpace-CRISis free, open source, compliant with openstandards, open protocols, open technologies.It provides institutions with a sustainable and effective tool to manage research information such as: researchers’ profiles, department pages, project grants & awards, research outputs, patents, theses, metrics, reports, statistics, etc.